PERSEPSI PENGENDARA SEPEDA MOTOR TERHADAP KESELAMATAN BERLALULINTAS BERDASARKAN THEORY PLANNED BEHAVIOR - Tangkudung, Ellen S.W.; Sampouw, Marcelino; Tjahjono, Tri (Jurnal Transportasi, 2010)
High numbers of dead and injury victims caused by road traffic accident can not be simply ignored. The National Accident data shows high percentage of motorcycle involved in accidents, with data in 2006 show more than 50% of the vehicles involved in accident are motorcycle. Human, vehicle, road, and environmental factors are major factors that cause accidents, but the most dominant factor is humanity. With the concept of